SURGICAL TREATMENT OF PATIENTS WITH ZYGOMATIC BONE INJURY - Alisher Shavkatovich Akhrorov; Fayzullaev Bunyod Abduminovich (Western European Studies, 2024)
The syndrome of mutual aggravation of injuries, which occurs as a result of multiple trauma, leads to a significant increase in the overall severity of the victim's condition. In order to determine the time of each stage of CFT treatment and reduce the number of complications, we have developed and introduced into clinical practice an algorithm for providing care for this injury. The tactics of treatment of patients with CTP, according to the developed algorithm, has an undoubted advantage over the previously used one - the percentage of inflammatory complications were reduced to a minimum: from 18% to 2%. Such an integrated approach increases the importance of triage of victims in order to achieve a therapeutic effect and economic result.
Keywords: midface injuries; surgical tactics; cerebrofacial trauma